Nanotribology of confined water by quasistatic computer simulations: effect of impurities - Pertsin, Alexander; Grunze, Michael (Tribology letters, 2010)
In our previous simulation study (Pertsin and Grunze, Langmuir 24:4750-4755, 2008), we have shown that water bilayer films confined between structured hydrophilic substrates can acquire the ability to sustain shear stress (i.e., to solidify), while remaining fluidlike in respect of the lateral order and molecular mobility. In this article, the previous simulations are extended to aqueous bilayer films containing simple model impurities. The shear behavior of the films is studied using the grand canonical Monte Carlo technique and quasistatic approach. It is found that the impurities tend to separate into an individual phase or to dissolve in water depending on the strength of the water-impurity interaction. In the former case, the effect of impurity on the shear modulus and yield stress is moderate and nearly linear in the concentration of impurity. In the latter case, the effect is noticeably stronger because the impurity distorts the local order and arrangement of water molecules, thus disturbing the local epitaxial coupling between the aqueous film and confining substrates. At the highest impurity content tried (~13%), the aqueous film loses most of its solidity and becomes practically fluidlike in respect to the shear response.